Use of Factory-Prepared Equimolar Mixture Nitrous Oxide/Oxygen in Paediatric Dentistry - J. Vašáková; Z. Teuberová; L. Navarová (Czech Dental Chamber, 2014)
Introduction and the aim: The work deals with the use of factory-prepared equimolar mixture nitrous oxide/oxygen (50 % N2O / 50 % O2) in the dental treatment of children. First of all the history and utilization of the nitrous oxide in the medicine is mentioned. The authors describe the physical properties and pharmacokinetics of nitrous oxide, which is the main part of the mixture. Further the work deals with indications and contraindications of the treatment using 50 % N2O / 50 % O2 with respect to the age of the child and to the extent and nature of the carried out procedure. The equipment, technology and course of administration in outpatient practice are described. The authors describe the technique of the administration factory-prepared equimolar mixture nitrous oxide/oxygen using inhalation through demand valve with the mouth piece or face mask. The most often side and undesirable effects of using the mixture are also mentioned, in addition to the impact of chronic exposure to nitrous oxide. The authors describe the technique of the administration factory-prepared 50 % N2O / 50 % O2 using inhalation demand valve with the mouth piece or face mask. Conclusion: Treatment of the children, especially for pre-school age, is often complicated by children's anxiosity from treatment. When psychotherapeutic approaches failed there isn't always choice of pharmacological approaches as conscious sedation by midazolam or general anesthesia in outpatient practice. Conscious inhalation sedation using the factory-prepared 50 % N2O / 50 % O2 so offers a fast, affordable and effective treatment option. The authors emphasize the complex treatment of a children patient, not only the partial treatment of carious lesions.